Conference report: Biocuration 2021 Virtual Conference. (9th April 2022) - Quaglia, Federica; Balakrishnan, Rama; Bello, Susan M; Vasilevsky, Nicole
Abstract: The International Society for Biocuration (ISB) aims to promote the field of biocuration and provide a community forum for information exchange and networking. Over the past 14 years, the ISB has hosted annual international conferences, entirely dedicated to the field of biocuration, that rotate between regions across the world. These meetings bring together biocurators from various roles, including database curators, bioinformaticians, ontology developers and students. Due to the ongoing global pandemic, the 14th Annual ISB Biocuration Conference (ISB2021) was held virtually in the form of four sessions and one workshop over the course of the year. Each of the four virtual sessions included panel discussions covering (i) The Future of Biocuration, (ii) Career paths and projections in Biocuration, (iii) Addressing Implicit or Unconscious Bias: Equity, Diversity and Inclusion and (iv) Strategic planning. Here we report on highlights from the virtual conference and share some of the ideas and future goals of the ISB. Database URL:https://www.biocuration.org/14th-annual-biocuration-conference-virtual/